Use of natural fibers in alternative wastewater treatment technologies, aiming at a more sustainable production: A review - Duarte, Eduarda Bertoletti; Rezende, Luciana Cristina Soto Herek (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The most worrisome issues today are the excessive production of solids in wastewater and the discharge of wastewater containing toxic components. Despite current environmental legislation, there are still difficulties in treating wastewater and properly disposing of the waste generated in the various stages of the production process to avoid inadequate and premature disposal that may pollute the environment. As a result, techniques are being developed to reuse wastewater differently, and in this scenario, natural fibers can be used to treat wastewater through an adsorption-based technique. Thus, this research has been developed from an exploratory bibliographic survey carried out according to scientific papers that used natural fibers as bioadsorbents in Scopus, ScienceDirect, Web of Science, and Capes databases. VOSviewer® software was used to create a cluster map to analyze the correlation between citations of selected papers. It was observed an increase in the number of research on the above topic over the years, especially in 2021. The most used natural fibers were plant-based, mostly cellulose. When evaluating the scientific contribution by country, Malaysia, India, and China were the most relevant. Brazil ranked fourth. Therefore, even with legislation on wastewater disposal and targets for the 2030 wastewater treatment plan, some countries are lagging in alternative techniques for the use of natural fibers in adsorption processes.